Validity and reliability of the Perceived Nutrition Environment Measures Survey (NEMS-P) for use in Brazil - Bruna Aparecida Avelar; Adriano Akira Ferreira Hino; Anabele Pires Santos; Larissa Loures Mendes; Júlia Cristina Cardoso Carraro; Raquel de Deus Mendonça; Mariana Carvalho de Menezes (Cambridge University Press, 2024)
Abstract Objective: The aim of this study is to evaluate the validity and reliability of the Perceived Nutrition Environment Measures Survey (NEMS-P) translated and adapted for use in Brazil. Design: Validation of the NEMS-P questionnaire. The questionnaires were applied to assess validity and reliability, based on exploratory factor analysis, Cronbach's α coefficient and intra-class correlation, with a significance level of 95 %. Setting: Brazil. Participants: Adults over 20 years of age diagnosed with hypertension were included in the internal validity and reliability test (n 176) and intra-rater reliability (subsample n 35). Results: Factor analysis obtained satisfactory results. Internal consistency was acceptable for most items, with Cronbach's α ranging from 0·6 to 0·9. The intra-rater reliability of the subsample was also valid, with intra-class correlation coefficient values ranging from 0·5 to 0·9. Conclusion: This work reveals the usefulness of the instrument to assess the perceived food environment in the Brazilian context, being able to measure what is proposed according to its theoretical model, and reproduces the values when applied to a sample different from its original validation. However, refinement of some questions is suggested. Finally, it demonstrates the possibility of using the entire instrument or each section independently, according to the food environments to be investigated.